The problem of thin plate stability at supersonic flow and presence of concentrated weight at edges - G. A. Samra (ՀՀ ԳԱԱ հրատ.)
Тhe stability problem of a thin plate with finite length, streamline gas is considered. А supersonic gas and the weight of a plate are neglected. But it is considered that there are concentrated weights on the fixed edge of a plate where the critical flow speeds causing flutter instability phenomenon are found. Դիտարկվում է գազի գերձայնային հոսքով շրջհոսվող վերջավոր երկարության բարակ սալի կայունության խնդիրը, սալի զանգվածը արհամարհվում է, սակայն համարվում է, որ սալի ամրակցված եզրերին կան նաև կենտրոնացած զանգվածներ, որոշված են ֆլաթերային անկայունության հանգեցնող շրջհոսման կրիտիկական արագությունները: Рассматривается задача устойчивости тонкой пластинки конечной длины, обтекаемой сверхзвуковым потоком газа. Масса пластинки пренебрегается, но считается, что на ее закрепленных кромках имеются сосредоточенные массы. Найдены критические скорости обтекания, приводящие к флаттерной неустойчивости.
Keywords: Technology; Mechanical engineering and machinery